Brillouin–Raman comb fiber laser with cooperative Rayleigh scattering in a linear cavity - Abdul Kadir @ Jaafar, Muhammad Zamzuri; Md Ali, Mas Izyani; Ahmad, A.; Mohamad, Romli; Mahdi, Mohd Adzir (Optical Society of America, 2006)
We demonstrate a multiple-wavelength Brillouin comb laser with cooperative Rayleigh scattering that uses Raman amplification in dispersion-compensating fiber. The laser resonator is a linear cavity formed by reflector at each end of the dispersion-compensating fiber to improve the reflectivity of the Brillouin Stokes comb. Multiple Brillouin Stokes generation has been improved in terms of optical signal-to-noise ratio and power-level fluctuation between neighboring channels. Furthermore, the linewidth of the Brillouin Stokes is uniform within the laser output bandwidth.